Proactively identifying the risks to performance in elite sport systems: A novel application of the Networked Hazard Analysis and Risk Management System (Net-HARMS) in women`s cycling - Hulme, A.; McLean, S.; Dallat, C.; Walker, G. H.; Waterson, P.; Stanton, N. A.; Salmon, P. M. (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2021)
There is increasing interest in applying systems Human Factors and Ergonomics (HFE) methods in sport. The Networked Hazard Analysis and Risk Management System (Net-HARMS) is a recently developed risk assessment (RA) approach that draws on systems HFE methods to identify risks across overall work systems. What makes Net-HARMS unique is its capacity to identify `emergent risks` - those unexpected risks that arise when risks from across the system combine and interact. Whilst the method was developed to support the identification of risks in safety-critical systems, its capacity to identify risks in other domains has been noted. This study sets out to use Net-HARMS in the context of elite women`s road cycling to predict all the credible risks that could degrade optimal sports performance. The findings demonstrate that Net-HARMS can be effectively applied in a context other than safety, and that multiple risks threatening the performance of the cycling team were identified.